Web-Scale Data Management for the Cloud - Lehner, Wolfgang; Sattler, Kai-Uwe.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
The efficient management of a consistent and integrated database is a central task in modern IT and highly relevant for science and industry. Hardly any critical enterprise solution comes without any functionality for managing data in its different forms. Web-Scale Data Management for the Cloud addresses fundamental challenges posed by the need and desire to provide database functionality in the context of the Database as a Service (DBaaS) paradigm for database outsourcing. This book also discusses the motivation of the new paradigm of cloud computing, and its impact to data outsourcing and service-oriented computing in data-intensive applications. Techniques with respect to the support in the current cloud environments, major challenges, and future trends are covered in the last section of this book. A survey addressing the techniques and special requirements for building database services are provided in this book as well.
Data Cloudification -- Virtualization for Data Management Services -- Transactional Data Management Services for the Cloud -- Web-Scale Analytics for BIG Data -- Cloud-specific Services for Data Management -- Overview and Comparison of Current Database-as-a-Service Systems -- Summary and Outlook.
Keywords: Computer science; Computer Communication Networks; Information systems; Database management; Computer Science; Database Management; Computer Communication Networks; Information Systems Applications (incl. Internet).; Information Systems and Communication Service